Improved post-transcriptional processing of an MDR1 retrovirus elevates expression of multidrug resistance in primary human hematopoietic cells - Knipper, Robert; Kuehlcke, K.; Schiedlmeier, Bernhard; Hildinger, M.; Lindemann, C.; Schilz, A. J.; Fauser, A. A.; Frühauf, Stefan; Zeller, W. Jens; Ostertag, W.; Eckert, H.-G.; Baum, C. (Gene therapy, 2001)
We describe the functional analysis of a novel retroviral vector, sf91m3, which was designed for improved expression of the in vivo selectable marker, multidrug resistance 1 gene (mdr1), in hematopoietic cells. Sf91m3 combines several promising features. The vector backbone lacks viral coding sequences and aug-start codons 5′ of the mdr1 cdna. A point mutation of a cryptic splice acceptor of the mdr1 cdna increases the probability of transferring an intact provirus. The titer of a pg13 packaging cell clone containing a single proviral integration is high (>2 × 106 particles/ml from frozen stocks of serum-free vector harvests). Human hematopoietic cells transduced with sf91m3 reliably express mdr1 before and after passage through nod/scid mice, as shown by quantitative pcr and efflux assays with rhodamine 123 or hoechst 33342. Finally, sf91m3 mediates resistance to escalated doses of cytotoxic agents, as shown by survival and differentiation of transduced colony-forming cells in the presence of colchicine at 48 ng/ml (>10 × IC50). Thus, SF91m3 may represent an interesting candidate for future trials addressing the safety and utility of MDR1 gene transfer; moreover, this study demonstrates that sequence alterations improving post-transcriptional processing of retroviral vectors have a substantial impact for gene expression in hematopoietic cells.
Gesehen am 20.01.2022